Upaya Pemberdayaan Masjid sebagai Pusat Kegiatan dan Layanan Sosial Kecamatan Alam Barajo Provinsi Jambi - Jamaluddin Arsyad; Zulqarnin; Arfan; Bujang Dek; Mares Zulpiar (Fakultas Dakwah UIN Sulthan Thaha Saifuddin Jambi, 2021)
Efforts to empower mosques are as centers of activities, both religious, educational and social services. But in reality, the function of the mosque with worldly dimensions does not have a maximum role in the development of the ummah and Islamic civilization. In order to preserve and develop mosques, it would require innovative thoughts and ideas as well as the will of all parties, especially the managers. The Miftahul Jannah Mosque, which is located in Kenalil Besar Alam Barajo, Jambi, is not only a place of worship, it has also functioned as a center for social activities and educational programs for local children. The forms of mentoring programs include: 1. Mosques as places of education and teaching, 2. As places for social and political activities, 3. Mosques as places for economic activities.